SITUATION ANALYSIS AND SPATIAL MAPPING STUDY OF STUNTING INCIDENTS IN TUBAN REGENCY, INDONESIA - Rahmawati, Deti; Sutikno; Saputro, Sigit Ari (Universitas Airlangga, 2025)
The prevalence of stunting in various regions of East Java, particularly in the Tuban Regency, necessitates targeted intervention. This study aimed to assess the incidence of stunting in Tuban Regency using diverse analytical methods. It utilizes geographic mapping to illustrate the spatial distribution of stunting rates, and histograms to represent the percentage of stunting across individual villages. Notably, Mander Village in Tambakboyo District exhibits the highest prevalence, with 43.59% of toddlers affected by stunting. In 2023, the average stunting rate across the Tuban Regency was 11.53% per village, with a median of 9.69%. Alarmingly, over half of the villages failed to meet the 2024 RPJMN target, and 112 of 328 communities (34.15%) reported stunting rates exceeding 14%. Furthermore, the analysis revealed a Moran's I value of 0.216 and a p-value of 0.001, indicating significant geographical clustering of stunting cases within the region. This suggests that the prevalence of stunted toddlers in each village is influenced by similar rates in neighboring communities, highlighting the importance of a collaborative approach in addressing this public health challenge.